Frequency of Successful Extubation in Patients with Rapid Shallow Breathing Maximum (RSBImax): Successful Extubation in Patients with RSBImax - Rabbani, Bushra; Umar, Mehrunnisa; Saeed, Ammarah; Ahmed, Ayaz; Yaseen, Mahjabeen; Waseem, Fahad (Pakistan Journal of Health Sciences, 2023)
Prolonged mechanical ventilation and premature removal from mechanical ventilation (MV) are independent risk factors for morbidity and mortality. Weaning and liberation from MV remain critical stages of a patient’s ICU stay. To date, no weaning predictive index has proven to be ideal. Objectives: To determine the frequency of successful extubation in patients on mechanical ventilation after 2 hour of spontaneous breathing trial (SBT). Methods: A total of 100 consecutive patients admitted in Medical ICU, meeting the inclusion criteria was enrolled. Non probability purposive sampling was employed. Patients of both gender and age >18 years, on mechanical ventilator for more than 48hrs were included. Two hours of SBT was performed in a semi seated position. RSBI were measured at 1 min after extubation. Patient who have not developed any feature of SBT intolerance, was continued on SBT up to 120 min. All collected data was entered into Statistical Package for Social Sciences (SPSS) version 24.0 for analysis. Results: Successful extubation was found to be (86%). in patients with RSBImax <105. Among 43 patients with successful extubation, 60.5% were male and 39.5% were female. The average age was 53+ 14.6 yrs and the average days of MV were 7+ 2.3 days. Rate of successful extubation was high with the age < 60 yrs, in male gender and with duration of MV <7 days. Conclusion: It is concluded from the above study that patients with RSBImax <105 were found to have successful extubation